PENGOLAHAN FRUIT LEATHER MANGGA GOLEK DI DESA MORNATEN, KECAMATAN TANIWEL KABUPATEN SERAM BAGIAN BARAT - Novalin Lawalata, Vita; Grace Sipahelut, Sophia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2022)
The purpose of implementing this service activity is to increase the knowledge and skills of the community in processing mango golek into fruit leather products in Mornaten Village, Taniwel District, West Seram Regency, Maluku Province. The target of this activity is aimed at the people of Mornaten Village. The methods used include counseling, training and evaluation activities. Through outreach activities, the community was given knowledge about the technology of processing mango golek into fruit leather products. Meanwhile, training activities are carried out by demonstrating directly to the community the technique of processing mango golek fruit leather. Based on the results of the service activities, it can be concluded that the purpose of the implementation of this service activity has been achieved and succeeded. The results of the evaluation showed that there was an increase in people's knowledge and skills about processing technology for mango golek fruit leather. This activity received a positive response from the community, this can be seen from the enthusiasm of the community during this activity.